More than skin‐deep: is basal cell carcinoma a marker for a cancer‐prone phenotype?. (27th February 2017) - Linos, E.; Bhatia, S.; Chren, M.M.
Abstract : Linked Article: Ransohoff et al. Br J Dermatol 2017; 176:512–516 .